An Illustrated Speculum Humanae Salvationis : Green Collection Ms 000321 - Nielsen, Melinda, (BRILL, 2022)
The medieval Latin poem Speculum Humanae Salvationis (known in English as The Mirror of Human Salvation ) was one of the most popular works of the fourteenth and fifteenth centuries with preachers and laity alike. Utilizing a typological approach to interpretation, it combines Old Testament and New Testament events and figures to depict an integrated narrative of redemption. As such, the Speculum is not only an outstanding model of medieval biblical interpretation, but also a fascinating case study in allegorical reading habits and the interplay between text and image. This Scholars Initiative project comprises the first modern transcription and English translation of the full Latin Speculum, accompanied by annotations tracing the biblical references and detailed notes explaining the visual iconography.